Religion and ideology in Assyria - Pongratz-Leisten, Beate (Boston Berlin De Gruyter, 2015)
Addressing the relationship between religion and ideology, and drawing on a range of literary, ritual, and visual sources, Beate Pongratz-Leisten argues that Assyria as a polity was as much exposed to (and influenced by) Babylonia in the south as it was to the Hittite and Hurrian cultural horizon in the north, and that this exposure was clearly reflected in the formulation and development of Assyria's royal ideology.
Frontmatter -- Acknowledgments -- Contents -- Abbreviations -- 1. Introduction -- 2. The Dynamics of Cultural Regions and Traditions in Mesopotamia and the Rise of Assyrian Cultural Discourse -- 3. The Origins of Assyrian Cultural Tradition -- 4. Empire as Cosmos, Cosmos as Empire -- 5. Narratives of Power and the Assyrian Notion of Kingship -- 6. Administrator, Hunter, Warrior: The Mythical Foundations of the King’s Role as Ninurta -- 7. The King’s Share in Divine Knowledge -- 8. Between the Fictive and the Imaginary -- 9. The Individual Ruler as a Model for Kingship: Rethinking Ancient Historiography -- 10. The Reinvention of Tradition: The Assyrian State Rituals -- 11. The Voice of the Scholar -- Appendix -- Bibliography
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Ideology -- Assyria; Monarchy -- Assyria; Ideology -- Assyria; Monarchy -- Assyria; Monarchy; Alte Geschichte, Archäologie; Ideology; Religion; HISTORY / Ancient / General; Assyria